How Cultural Perceptions and Food Preparation Affect Westerners View of Insects as Food - Grosdidier, Raymond; Wood, Spencer; Marshall, Jeremy (My University, 2018)
There has been a recent push to encourage westerners to introduce insects into their diets. Traditional arguments that stress environmental and nutritional benefits have been largely unsuccessful. This not because people simply find insects distasteful; what people view as an acceptable food choice is culturally dependent, and foods made from novel and unfamiliar ingredients or tools are met with apprehension. What is less known is why insects are viewed as an unacceptable food source in western society. It has been suggested that westerners disgust towards insects is that insects are perceived of as contaminants and as vectors of disease. If westerners are unwilling to eat insects, or food prepared with insects because they are viewed as unhygienic, then we should expect individuals who are less concerned with hygiene to be more willing to eat insects, or food prepared with insects. When surveyed on their hygiene and their willingness to try food prepared using insects, participants that were less concerned with personal hygiene were more willing to eat food made with insects. In order to convince people to introduce insects into their diet one must know why people are so uneager to consume insects.
Keywords: Fall 2018